Cytotoxicity activity of ethanol extract of mentangor stem skin (Calophyllum rufigemmatum) against breast cancer cells MCF-7 in vitro: Chemistry - Widia Widia; Eresti Ependi; Addela Amelia; Candra Candra; Occa Roanisca (Jurnal Pijar Mipa, 2023)
Cancer is one of the non-communicable diseases that causes the most death in Indonesia. In a study conducted by researchers from Northwestern University on 686 breast cancer patients, 36% of women chose to stop their treatment because they could not tolerate the side effects of the drug. The patient's side effects were joint pain, hot flashes, increased weight gain, and nausea. Mentangor plant (Calophyllum rufigemmatum) is a plant that grows a lot in Bangka Belitung and has been used by the people of Bangka Belitung as a traditional medicine to treat skin diseases. Research on the bark of the mentangor stem from Bangka Belitung has never been carried out regarding its phytochemical content and potential as an anticancer breast. For this reason, it is necessary to know breast cancer's pharmacological effects and phytochemicals on Mentangor Bangka Belitung's stem bark. Phytochemical identification was carried out qualitatively by observing changes in the test sample. Based on the results of phytochemical screening, several reactions showed that each test of the ethanol extract of the stem bark of Mentangor contained tannins, phenolics, flavonoids, and alkaloids. The measurement results of the IC50 value of inhibition of the proliferation ethanol extract with a diameter of 1 cm, 7 cm, and 17 cm against MCF-7 breast cancer cells were 326,195 g/mL, respectively; 186.178 g/mL; and 178.090 g/mL.